Mal de debarquement syndrome: new insights - Cha, Yoon-Hee (Ann N Y Acad Sci, 2015)
Mal de debarquement syndrome (MdDS) is an enigmatic neurotological disorder with high morbidity, psychosocial burden, and few treatment options. Fortunately, there has been recent growth in scientific interest in understanding the biological basis of and in treating MdDS. Recent studies using functional neuroimaging have shown increased glucose metabolism in the left entorhinal cortex and amygdala in the setting of decreased prefrontal and temporal cortex metabolism in subjects with persistent MdDS. The entorhinal cortex is a key player in processing and gating spatial information to be stored in the hippocampus and is a major driver of brain oscillations. A limbic focus may also be key to spontaneous MdDS-like symptoms occurring in individuals with a history of anxiety or chronic stress. Treatment with repetitive transcranial magnetic stimulation over the dorsolateral prefrontal cortex can decrease the rocking dizziness of MdDS, with successful responses associated with decreases in the coherence between brain networks with nodes in the parietal and occipital lobes. A new theory of MdDS is proposed as pathology secondary to entrainment of intrinsic brain networks driven by oscillatory motion exposure coupled with an inability to subsequently desynchronize the activity of these nodes. Future treatment strategies may be directed toward unyoking these networks.